The Effect of Entrepreneurial Knowledge and Individual Creativity on Students’ Entrepreneurial Intention and Self-Efficacy - Vita Yanna Anita Dewi; Fereshti Nurdiana Dihan (ELRISPESWIL - Lembaga Riset dan Pengembangan Sumberdaya Wilayah, 2026)
This study aims to examine the influence of entrepreneurial knowledge and individual creativity on students’ entrepreneurial intention, with self-efficacy serving as a mediating variable. The research employed a quantitative approach using a causal associative design involving students of the Management Study Program, Faculty of Business and Economics, Universitas Islam Indonesia, cohort 2021. A total of 78 respondents were selected through purposive sampling, with the criterion that participants had completed an entrepreneurship course. Data were collected using a structured questionnaire measured on a five-point Likert scale and analyzed through Partial Least Squares–Structural Equation Modeling (PLS-SEM) using SmartPLS 4.0. The findings reveal that entrepreneurial knowledge and individual creativity have positive and significant effects on both self-efficacy and entrepreneurial intention. Furthermore, self-efficacy demonstrates a positive and significant effect on entrepreneurial intention and mediates the relationship between entrepreneurial knowledge, individual creativity, and entrepreneurial intention (partial and full mediation). The coefficient of determination (R²) of 0.645 indicates that the proposed model explains 64.5% of the variance in entrepreneurial intention. These results underscore the importance of strengthening students’ self-efficacy within entrepreneurship education to enhance entrepreneurial intention.